Chapter Postfazione. Il socialismo di Bruno Trentin come liberazione della persona - Mari, Giovanni (Studi e saggi, 2021)
Through the commentary on a particularly interesting period taken from the Introduction to La libertà viene prima, the author intends to focus on Bruno Trentin's idea of socialism. Giovanni Mari underlines how this idea foresees the critique of four theses of the modern socialist tradition: 1) socialism is not a model of society, but a continuous process; 2) in our company the company does not constitute a world in itself; 3) the socialization of property does not solve the problems of democracy; 4) the center of civil coexistence is not constituted by the class but by the person. And four positive theses: 1) the form of political action does not foresee two separate times, first the seizure of power and then the reforms; 2) the measure of society is the freedom of the person; 3) the goal of the socialist process is the self-realization of the person; 4) everything begins with the person who works, that is, with the battle for freedom in work.